2014
DOI: 10.1371/journal.pone.0095333
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Calcite Crystal Morphology Is Modulated by Otoconial Proteins Otolin-1 and Otoconin-90

Abstract: Otoconia are formed embryonically and are instrumental in detecting linear acceleration and gravity. Degeneration and fragmentation of otoconia in elderly patients leads to imbalance resulting in higher frequency of falls that are positively correlated with the incidence of bone fractures and death. In this work we investigate the roles otoconial proteins Otolin-1 and Otoconin 90 (OC90) perform in the formation of otoconia. We demonstrate by rotary shadowing and atomic force microscopy (AFM) experiments that O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Oc90 and Otolin cooperate to synergistically facilitate matrix calcification in cultured cells (Yang et al, 2011b). In vitro , Oc90 requires the presence of Otolin to generate crystals with otoconia-like morphology (Moreland et al, 2014). Similarly, the normal growth of zebrafish otoliths requires OMP-1 and its incorporation of Otolin1a (Murayama et al, 2005; Murayama et al, 2004).…”
Section: Constituent Proteins In Otoconia and Otolith Developmentmentioning
confidence: 99%
“…Oc90 and Otolin cooperate to synergistically facilitate matrix calcification in cultured cells (Yang et al, 2011b). In vitro , Oc90 requires the presence of Otolin to generate crystals with otoconia-like morphology (Moreland et al, 2014). Similarly, the normal growth of zebrafish otoliths requires OMP-1 and its incorporation of Otolin1a (Murayama et al, 2005; Murayama et al, 2004).…”
Section: Constituent Proteins In Otoconia and Otolith Developmentmentioning
confidence: 99%
“…Otolin-1 requires OMP-1 in zebrafish or Oc90 in mice in order to be included into the biomineral organic matrix [12,21]. It was also shown that otolin-1 is capable of forming a filamentous network similar to that formed by collagen X [38,39]. In a vapour diffusion assay, recombinant otolin-1 had a significant effect on the shape of calcium carbonate crystals, apparently through the anisotropic acceleration of the crystallization of calcite.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins have a globular C1q-like domain, which has tremendous potential to interact with other biomolecules [41][42][43]. Atomic force microscopy and electron microscopy studies have shown that mammalian otolin-1 may be involved in the formation of a hexagonal framework inside otoconia, in which otolin-1 chains may be interconnected by the C1q-like domain [39]. Atomic force microscopy and electron microscopy studies have shown that mammalian otolin-1 may be involved in the formation of a hexagonal framework inside otoconia, in which otolin-1 chains may be interconnected by the C1q-like domain [39].…”
Section: Introductionmentioning
confidence: 99%
“…These proteins include otoconin‐90 (OC90), collagenous scaffold protein otolin‐1, otopetrin, fetuin‐A, and cerebellin‐1 . Otoconin‐90 accounts for 90% of the total protein in the organic core of the otoconia, and together with otolin, forms iso‐oriented columns of nano‐crystals, which then results in the complex mosaic of native otoconia . Fetuin‐A and osteopontin are also believed to regulate nucleation and growth of calcite .…”
Section: Introductionmentioning
confidence: 99%
“…13 From the Department of Otolaryngology (W.T.K.K., R Otoconin-90 accounts for 90% of the total protein in the organic core of the otoconia, [12][13][14]16,18 and together with otolin, forms iso-oriented columns of nano-crystals, which then results in the complex mosaic of native otoconia. 16,19 Fetuin-A and osteopontin are also believed to regulate nucleation and growth of calcite. 20 Otopetrin 1 has been demonstrated to regulate cytosolic concentrations of calcium during otoconial mineralization.…”
Section: Introductionmentioning
confidence: 99%